Rapid preparation method of nano metal film
By using carbon nanotube film and Joule heating technology, nanometal films are rapidly prepared, which solves the problems of environmentally friendly, time-consuming and high equipment costs in the existing technology, and achieves efficient, environmentally friendly and diversified preparation of metal films. .
Patent Information
- Application Number
- CN202411552414.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-14
AI Technical Summary
The existing metal film preparation methods have environmental protection problems, are time-consuming and have high equipment costs, making it difficult to achieve rapid, pollution-free, low equipment cost and diverse types of coatings.
Using the own characteristics of the carbon nanotube film, the metal target is quickly plated on the substrate in the form of nanoparticles, thereby achieving rapid preparation of nanometal films.
It realizes the rapid preparation of metal films, which are simple and fast, pollution-free, low equipment cost, and diverse types of coatings, significantly improving the preparation efficiency and product uniformity and controllability.
Smart Images

Figure CN119433452A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal film preparation, and in particular to a method for quickly preparing a nano metal film. Background Art
[0002] In the context of the rapid development of modern science and technology, the preparation of metal films has become an important research direction in the field of materials science and engineering. Metal films are widely used in many fields such as electronic devices, optical devices, sensors, and catalysts due to their excellent electrical conductivity, thermal conductivity, and chemical stability. With the continuous advancement of microelectronics and nanotechnology, the demand for metal films is increasing, which has promoted the innovation and development of their preparation technology.
[0003] Metal films not only play a key role in integrated circuits and microelectromechanical systems (MEMS), but also show great application potential in optical coatings, anti-corrosion coatings and thermal management materials. Due to their unique physical and chemical properties, metal films have irreplaceable advantages in improving device performance, extending material life and realizing new functions.
[0004] Metal film is a new type of film material. Compared with traditional transparent insulating media and polymer films, it has the advantages of higher mechanical strength, better toughness, and better thermal and electrical conductivity. Among them, copper has low cost and high electrical conductivity, second only to silver, which makes it extremely advantageous in electrical connections and wire applications. At the same time, copper has high thermal conductivity, which helps to effectively dissipate heat and ensure the stable operation of electronic devices under high load conditions. Therefore, the application prospects of copper film in emerging fields such as flexible electronics and smart wearable devices are becoming more and more broad. In addition, aluminum, as the most widely used metal material, has huge application potential. It has good corrosion resistance and electrical conductivity, light weight, small thickness, high reflectivity in the infrared light region, and has the potential to be used as an infrared stealth film. Its reflective properties make it an ideal material for optical mirrors and reflectors, and it is widely used in lasers, optical sensors, solar cells and other equipment. Therefore, the application of aluminum film in nanostructure and functionalization shows broad prospects.
[0005] At present, there are many methods for preparing metal films, mainly including electroplating, chemical methods, and physical methods. However, electroplating and chemical deposition methods are prone to produce harmful substances and pollute the environment. In comparison, the magnetron sputtering technology in the physical deposition method is more environmentally friendly, but it takes a long time and has low bonding degree and is prone to instability. The electroplating process has a long history. With the popularization of metal plating applications, scholars at home and abroad have conducted more and more in-depth research on the electroplating process. The electroplating process has been widely used in traditional metal processing. It uses the principle of electrolysis to deposit metal ions on the surface of conductive materials to form corresponding metal films. Electroplating is used in various fields, such as improving conductivity, wear resistance, oxidation resistance, and corrosion resistance. Compared with other preparation methods, the advantages of electroplating are simple equipment, low energy consumption, and easy mass production. Compared with electroplating, chemical plating is a surface treatment method that uses reducing ions to deposit metal cations on the plated substrate without external current. Studies have shown that the coating obtained by chemical plating is more uniform and the surface of the coating is also smoother. In addition, chemical plating has no restrictions on the substrate to be plated, and does not require a high difference in electrical properties between the substrate to be plated and the plated metal. More importantly, both conductors and non-conductor substrates can be deposited with metal coatings. The chemical plating process does not require expensive equipment, only specific chemicals need to be dissolved and mixed in proportion and maintained at a specific ambient temperature for a period of time. Physical plating is a process in which the coating material is deposited and thickened on the substrate surface as gas-phase atoms or ions to form a uniform coating layer. Compared with chemical plating, its deposition rate and film density are higher than chemical plating, and the bonding with the substrate is also more stable.
[0006] In summary, electroplating and chemical deposition methods are prone to produce harmful substances, pollute the environment, and have certain requirements for substrates. In comparison, magnetron sputtering technology in physical deposition methods is more environmentally friendly, but physical deposition takes a long time and has a low degree of bonding, is easily unstable, and has expensive equipment and high requirements. Therefore, it is urgent to develop a simple, fast, pollution-free, low-cost equipment method for coating metal nanoparticles and their composite films with a variety of coating types. Summary of the invention
[0007] The present invention provides a method for rapidly preparing nano-metal thin films, which can utilize the characteristics of carbon nanotube films to achieve the purpose of instantaneous heating coating, and coat the metal target material on a substrate in the form of nanoparticles. Compared with traditional coating methods, the coating technology of the present invention is simple, fast, pollution-free, has low equipment cost, and has a variety of coating types.
[0008] A method for rapidly preparing a nano-metal film, characterized in that it comprises the following steps:
[0009] S1: acidifying the nanocarbon film, then washing and drying it;
[0010] S2: preparing a metal particle dispersion;
[0011] S3: placing a metal particle dispersion on the dried nano-carbon film for loading, and taking it out after drying to obtain a nano-carbon film loaded with a metal particle raw material layer;
[0012] S4: placing the nanocarbon film loaded with the metal particle raw material layer between two electrodes in the Joule heat heating chamber, and connecting two ends of the nanocarbon film to the two electrodes respectively;
[0013] S5: placing the substrate on the nanocarbon film loaded with the metal particle raw material layer without contacting it;
[0014] S6: evacuating the Joule heat heating chamber and applying voltage to the nano-carbon film through a power supply to generate Joule heat, so that the metal particles on the nano-carbon film evaporate to the lower surface of the substrate;
[0015] S7: Remove the voltage to obtain a nano-metal film.
[0016] In the step S1, the acidification treatment refers to treatment with nitric acid.
[0017] In the step S2, the metal particle dispersion is prepared by placing metal particles in deionized water, stirring and then ultrasonically dispersing to obtain the dispersion, and the metal particle material is one of copper, zinc, aluminum, titanium and tungsten.
[0018] In the step S3, the metal particle dispersion refers to an aqueous ion dispersion of copper powder, zinc powder, aluminum powder, titanium powder or tungsten powder.
[0019] In the step S5, the substrate is placed 5-8 mm above the nano-carbon film loaded with the metal particle raw material layer.
[0020] In the step S6, the Joule heat heating chamber is evacuated to 10 -1 Below Pa.
[0021] In the step S5, the substrate material is a carbon nanotube film, a silicon wafer, a non-conductive glass sheet, a ceramic, or a plastic; in the step S6, a voltage is applied to the nanocarbon film through a power source to generate Joule heat, so that the surface temperature of the nanocarbon film reaches 850°C-1050°C, and the metal particles evaporate to the lower surface of the substrate.
[0022] In the step S1, the nanocarbon film refers to one of a carbon nanotube film, a graphene film, a MXene film, and a carbon fiber film.
[0023] The loading of a certain amount of metal particle dispersion on the acidified nano-carbon film is achieved by suction filtration or coating.
[0024] The present invention also provides another method for rapidly preparing a nano-metal film, which is characterized by comprising the following steps:
[0025] S1: acidifying the nanocarbon film, then washing and drying it;
[0026] S2: Take the metal foil for use;
[0027] S3: placing the nanocarbon film between two electrodes in a Joule heat heating chamber, connecting two ends of the nanocarbon film to the two electrodes respectively, and placing a metal foil on top of the nanocarbon film;
[0028] S4: Place the substrate on top of the metal foil without contacting it;
[0029] S5: evacuating the Joule heat heating chamber and applying voltage to the nano-carbon film through a power supply to generate Joule heat, so that the metal elements on the metal foil evaporate to the lower surface of the substrate;
[0030] S6: Remove the voltage to obtain a nano-metal film.
[0031] In the step S1, the nanocarbon film refers to one of a carbon nanotube film, a graphene film, a MXene film, and a carbon fiber film, and the acidification treatment refers to treatment with nitric acid;
[0032] In the step S2, the metal foil refers to copper foil;
[0033] In the step S4, the substrate is placed 5-8 mm above the metal foil; the substrate material is a carbon nanotube film, a silicon wafer, a non-conductive glass sheet, ceramics, or plastic;
[0034] In the step S5, the Joule heat heating chamber is evacuated to 10 -1 Pa, and applying voltage to the nano-carbon film through a power source to generate Joule heat; the surface temperature of the nano-carbon film reaches 850° C.-1050° C., so that the metal elements on the metal foil evaporate to the lower surface of the substrate.
[0035] The above technical solutions show that:
[0036] 1. The Joule heat generated in a short time for rapid coating proposed by the present invention is simple, efficient and easier to operate compared to traditional vapor deposition. For vacuum evaporation and chemical vapor deposition, when the substrate and raw materials are the same, the target metal oxide film can be obtained within a few seconds by Joule heating, which is significantly more efficient than the traditional coating process that takes tens of minutes or even hours.
[0037] 2. From the perspective of film morphology, the metal film prepared by the method proposed in the present invention has better particle size distribution uniformity and controllable size compared to the film prepared by the electrodeposition method, and the film thickness can be adjusted by controlling the voltage or deposition time.
[0038] 3. The method of the present invention has been verified to be applicable to the rapid preparation of metal thin films such as Cu, Al, Zn, Ti, and W, and the substrates have been tried such as silicon wafers, ceramics, glass, carbon materials, and plastics. In addition, the film materials and substrates used are of various sizes. Therefore, the film materials and substrates are adjustable in size and of various types. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0040] Figure 1 Diagram of the preparation of metal nanofilm.
[0041] Figure 2 Scanning electron microscope image of the surface of a copper-coated carbon nanotube film.
[0042] Figure 3 Scanning electron microscope image of a silicon wafer surface coated with copper.
[0043] Figure 4 Scanning electron microscope image of the surface of a glass sheet coated with copper.
[0044] Figure 5 Scanning electron microscope image of the surface of a carbon nanotube film coated with copper foil.
[0045] Figure 6 Scanning electron microscope image of the surface of carbon nanotube film coated with aluminum foil.
[0046] Figure 7 Scanning electron microscope image of the surface of a titanium-coated carbon nanotube film.
[0047] Figure 8 Scanning electron microscope image of the surface of a carbon nanotube film coated with tungsten.
[0048] Fig. 9 Scanning electron microscope image of a silicon wafer surface coated with tungsten.
[0049] Fig.10 General EDS spectrum of the surface of a copper-plated silicon wafer.
[0050] Fig.11 XPS overall spectrum of the copper-coated carbon nanotube film surface.
[0051] Fig.12 High-resolution transmission electron microscopy image of copper plated on the surface of carbon nanotube film.
[0052] Fig.13The present invention is a flowchart of a method for rapidly preparing a nano-metal film. DETAILED DESCRIPTION
[0053] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0054] See also Figure 1 , Fig.13 The present invention provides a method for rapidly preparing a nano-metal film, comprising the following steps:
[0055] S1: soaking the nano-carbon film 3 in nitric acid for a certain period of time for acidification, then rinsing with deionized water and drying;
[0056] S2: preparing a metal particle dispersion;
[0057] S3: loading a certain amount of metal particle dispersion on the nano-carbon film 3 treated with nitric acid, and taking it out after drying;
[0058] S4: placing the nanocarbon film 3 loaded with the metal particle raw material layer between two electrodes 4 in the Joule heat heating chamber, and connecting two ends of the nanocarbon film 3 to the two electrodes 4 respectively;
[0059] S5: Take a substrate 1 and place it on the nano-carbon film 3 loaded with the metal particle raw material layer without contacting it;
[0060] S6: evacuating the Joule heat heating chamber and applying pressure through a power supply, so that the nano-carbon film 3 generates Joule heat, and the metal particles on the nano-carbon film 3 evaporate to the lower surface of the substrate 1;
[0061] S7: Remove the voltage to obtain a nano-metal film.
[0062] Among them, the metal raw material can be powder or sheet. For the metal sheet, it is first cleaned, washed, dried and placed on the surface of the carbon nanotube film; for the metal powder, it is dispersed to prepare a metal particle dispersion, and then the metal source is loaded on the carbon nanotube film and dried for use; electricity is passed through both ends of the carbon nanotube film loaded with the metal source to generate Joule heat, and the metal target material loaded on the surface of the carbon nanotube film is instantly plated on the substrate in the form of nanoparticles to obtain a metal nanofilm.
[0063] Alternatively, prepare a metal foil 2 for standby use; place the metal foil 2 on the nanocarbon film 3 prepared in step S1. Place the nanocarbon film 3 between two electrodes 4 in a Joule heat heating chamber, connect the two ends of the nanocarbon film 3 to the two electrodes 4 respectively, and place the metal foil 2 on top of the nanocarbon film 3; take the substrate 1 and place it on top of the metal foil 2 without contact; evacuate the Joule heat heating chamber and apply voltage to the nanocarbon film 3 through a power supply to generate Joule heat; so that the metal elements on the metal foil 2 evaporate to the lower surface of the substrate 1;
[0064] Example 1:
[0065] Soak a carbon nanotube membrane with a size of 1×3cm and a thickness of 20μm in nitric acid for 6h, then rinse it with deionized water 3 times and dry it. Dissolve 0.5g of copper powder in 100mL of deionized water, stir for 5 minutes, and ultrasonicate for half an hour to obtain a dispersion with a concentration of 5mg / mL. Then filter 5mL of the above solution on the carbon nanotube membrane washed with nitric acid for loading. Take it out after drying, and place it between the two electrodes in the Joule heat heating chamber, and connect the two ends of the carbon nanotube membrane to the two electrodes with conductive silver glue. Further, place another carbon nanotube membrane 5mm above the carbon nanotube membrane loaded with the copper powder raw material layer. Further, evacuate the chamber to 10 -1 Pa, and keep the vacuum pumping continuously, apply a constant voltage of 20V between the two electrodes, and keep it for 1s. After removing the voltage, a metal film composed of nano copper powder particles is evenly deposited on the lower surface of the upper carbon nanotube film, and a nano copper metal film is obtained. Figure 2 , Fig.11 , Fig.12 .
[0066] Example 2:
[0067] Soak a carbon nanotube membrane with a size of 1.5×3.5cm and a thickness of 20μm in nitric acid for 6h, then rinse it with deionized water three times and dry it. Dissolve 0.2g of copper powder in 50mL of deionized water, stir for 5 minutes, and ultrasonicate for half an hour to obtain a dispersion with a concentration of 4mg / mL. Then filter 6mL of the above solution on the carbon nanotube membrane washed with nitric acid for loading. Take it out after drying and place it between the two electrodes in the Joule heat heating chamber. Use conductive silver glue to connect the two ends of the carbon nanotube membrane to the two electrodes respectively, and then place a silicon wafer 5mm away from the carbon nanotube membrane. Further, evacuate the chamber to 10 -1 Pa, and keep the vacuum pumping continuously, apply a constant voltage of 15V between the two electrodes, and keep it for 1s, the lower copper particles are evaporated evenly to the lower surface of the silicon wafer. Figure 3 .
[0068] Example 3:
[0069] Soak a carbon nanotube membrane with a size of 1.5×2cm and a thickness of 20μm in nitric acid for 6h, then rinse it with deionized water three times and dry it. Dissolve 0.6g of copper powder in 120mL of deionized water, stir for 5 minutes, and ultrasonicate for half an hour to obtain a dispersion with a concentration of 5mg / mL. Then filter 4mL of the above solution on the carbon nanotube membrane washed with nitric acid for loading. After drying, take it out and place it between the two electrodes in the Joule heat heating chamber. Use conductive silver glue to connect the two ends of the carbon nanotube membrane to the two electrodes respectively, and then place a non-conductive glass sheet 5mm away from the carbon nanotube membrane. Further, evacuate the chamber to 10 -1 Pa, and keep the vacuum pumping continuously, apply a constant voltage of 23V between the two electrodes, and keep it for 3s, the lower copper particles are evaporated evenly to the lower surface of the glass sheet. Figure 4 .
[0070] Example 4:
[0071] A copper foil with a size of 1×2cm and a thickness of 0.05mm was soaked in ethanol for 3 times and dried. A carbon nanotube film with a size of 1.5×3cm and a thickness of 20μm was soaked in nitric acid for 6h, then soaked in deionized water for 3 times and dried. The carbon nanotube film washed with nitric acid was placed between the two electrodes in the Joule heat heating chamber, and the two ends of the carbon nanotube film were connected to the two electrodes respectively with conductive silver glue, and the cleaned copper foil was placed directly on the lower carbon nanotube film. Furthermore, a carbon nanotube film with a size of 1×3cm and a thickness of 10μm was placed 5mm away from the 20μm carbon nanotube film. Reach 10 -1 Pa vacuum degree, and then pressurize by power supply. Under 40V constant voltage, keep for 2s, the surface of carbon nanotube film reaches 850℃, and the copper particles in the lower layer are uniformly evaporated to the lower surface of the upper carbon nanotube film. Figure 5 .
[0072] Example 5:
[0073] A copper foil with a size of 1×3cm and a thickness of 0.1mm was soaked in ethanol for 3 times and dried. A carbon nanotube film with a size of 1.5×4cm and a thickness of 20μm was soaked in nitric acid for 6 hours, then soaked in deionized water for 3 times and dried. The carbon nanotube film washed with nitric acid was placed between the two electrodes in the Joule heat heating chamber, and the two ends of the carbon nanotube film were connected to the two electrodes respectively with conductive silver glue, and the cleaned copper foil was placed directly on the lower carbon nanotube film. Furthermore, a carbon nanotube film with a size of 1.5×4cm and a thickness of 10μm was placed 5mm away from the 20μm carbon nanotube film. Reaching 10 -1 After the vacuum degree reaches Pa, the power supply is used to pressurize the film. At a constant voltage of 50V, the temperature of the carbon nanotube film surface reaches 1050℃, and the copper particles in the lower layer are uniformly evaporated to the lower surface of the upper carbon nanotube film.
[0074] Example 6:
[0075] A copper foil with a size of 1.5×3cm and a thickness of 0.2mm was soaked in ethanol for 3 times and dried. A carbon nanotube film with a size of 2×4cm and a thickness of 20μm was soaked in nitric acid for 6h, then soaked in deionized water for 3 times and dried. The carbon nanotube film washed with nitric acid was placed between two electrodes in a Joule heat heating chamber, and the two ends of the carbon nanotube film were connected to the two electrodes respectively with conductive silver glue, and the cleaned copper foil was placed directly on the lower carbon nanotube film. Furthermore, a carbon nanotube film with a size of 2×4cm and a thickness of 10μm was placed 5mm away from the 20μm carbon nanotube film. Reaching 10 -1 After the vacuum degree reaches Pa, the power supply is used to pressurize the film. At a constant voltage of 55V, the temperature is maintained for 2 seconds, and the surface of the carbon nanotube film reaches 970°C. The copper particles in the lower layer are uniformly evaporated to the lower surface of the upper carbon nanotube film.
[0076] Example 7:
[0077] A zinc foil with a size of 1×2cm and a thickness of 0.2mm was soaked in ethanol for 3 times and dried. A carbon nanotube film with a size of 2×3cm and a thickness of 20μm was soaked in nitric acid for 6h, then soaked in deionized water for 3 times and dried. The carbon nanotube film washed with nitric acid was placed between the two electrodes in the Joule heat heating chamber, and the two ends of the carbon nanotube film were connected to the two electrodes respectively with conductive silver glue, and the washed zinc foil was placed directly on the lower carbon nanotube film. Furthermore, a carbon nanotube film with a size of 2×3cm and a thickness of 10μm was placed 5mm away from the 20μm carbon nanotube film. Reaching 10 -1 Pa vacuum is then applied with a power supply. At a constant voltage of 40 V, the carbon nanotube film surface reaches 1030°C for 5 seconds, and the lower zinc particles are uniformly evaporated to the lower surface of the upper carbon nanotube film.
[0078] Example 8:
[0079] An aluminum foil with a size of 1×3cm and a thickness of 0.2mm was soaked in ethanol for 3 times and dried. A carbon nanotube film with a size of 2×4cm and a thickness of 20μm was soaked in nitric acid for 6h, then soaked in deionized water for 3 times and dried. The carbon nanotube film washed with nitric acid was placed between the two electrodes in the Joule heat heating chamber, and the two ends of the carbon nanotube film were connected to the two electrodes respectively with conductive silver glue, and the washed aluminum foil was placed directly on the lower carbon nanotube film. Further, another carbon nanotube film was placed 5mm above the carbon nanotube film loaded with aluminum foil. Further, the chamber was evacuated to 10 -1Pa, and keep the vacuum pumping continuously, apply a constant voltage of 20V between the two electrodes, and keep it for 1s. After removing the voltage, a metal film composed of nano-aluminum powder particles is evenly deposited on the lower surface of the upper carbon nanotube film, and a nano-aluminum metal film is obtained. Figure 6 .
[0080] Example 9:
[0081] Soak a carbon nanotube membrane with a size of 1×2cm and a thickness of 20μm in nitric acid for 6h, then rinse it with deionized water three times and dry it. Dissolve 0.4g of titanium powder in 80mL of deionized water, stir for 5 minutes, and ultrasonicate for half an hour to obtain a dispersion with a concentration of 5mg / mL. Then filter 5mL of the above solution on the carbon nanotube membrane washed with nitric acid for loading. Take it out after drying, and place it between the two electrodes in the Joule heat heating chamber, and connect the two ends of the carbon nanotube membrane to the two electrodes respectively with conductive silver glue. Further, place another carbon nanotube membrane 5mm above the carbon nanotube membrane loaded with the titanium powder raw material layer. Further, evacuate the chamber to 10 -1 Pa, and keep the vacuum pumping continuously, apply a constant voltage of 50V between the two electrodes, and keep it for 3s. After removing the voltage, a metal film composed of nano-titanium powder particles is evenly deposited on the lower surface of the upper carbon nanotube film to obtain a nano-titanium metal film. Figure 7 .
[0082] Example 10:
[0083] Soak a carbon nanotube membrane with a size of 2×4cm and a thickness of 20μm in nitric acid for 6h, then rinse it with deionized water three times and dry it. Dissolve 0.5g of tungsten powder in 200mL of deionized water, stir for 5 minutes, and ultrasonicate for half an hour to obtain a dispersion with a concentration of 2.5mg / mL. Then filter 10mL of the above solution on the carbon nanotube membrane washed with nitric acid for loading. Take it out after drying, and place it between the two electrodes in the Joule heat heating chamber, and connect the two ends of the carbon nanotube membrane to the two electrodes respectively with conductive silver glue. Further, place another carbon nanotube membrane 5mm above the carbon nanotube membrane loaded with the tungsten powder raw material layer. Further, evacuate the chamber to 10 -1 Pa, and keep the vacuum pumping continuously, apply a constant voltage of 22V between the two electrodes, and keep it for 1s. After removing the voltage, the metal film composed of nano-tungsten powder particles is evenly deposited on the lower surface of the upper carbon nanotube film to obtain a nano-tungsten metal film. Figure 8 .
[0084] Example 11:
[0085] Soak a carbon nanotube membrane with a size of 1×3cm and a thickness of 20μm in nitric acid for 6h, then rinse it with deionized water three times and dry it. Dissolve 0.2g of tungsten powder in 50mL of deionized water, stir for 5 minutes, and ultrasonicate for half an hour to obtain a dispersion with a concentration of 4mg / mL. Then filter 5mL of the above solution on the carbon nanotube membrane washed with nitric acid for loading. Take it out after drying and place it between the two electrodes in the Joule heat heating chamber. Use conductive silver glue to connect the two ends of the carbon nanotube membrane to the two electrodes respectively, and then place a silicon wafer 5mm away from the carbon nanotube membrane. Further, evacuate the chamber to 10 -1 Pa, and keep the vacuum pumping continuously, apply a constant voltage of 15V between the two electrodes, and keep it for 1s. After removing the voltage, the metal film composed of nano-tungsten powder particles is evenly deposited on the lower surface of the upper silicon wafer to obtain a nano-tungsten metal film. Fig. 9 .
[0086] Example 12:
[0087] Soak a carbon nanotube membrane with a size of 1.5×3.5cm and a thickness of 20μm in nitric acid for 6h, then rinse it with deionized water three times and dry it. Dissolve 0.5g of tungsten powder in 100mL of deionized water, stir for 5 minutes, and ultrasonicate for half an hour to obtain a dispersion with a concentration of 5mg / mL. Then filter 4mL of the above solution on the carbon nanotube membrane washed with nitric acid for loading. Take it out after drying and place it between the two electrodes in the Joule heat heating chamber. Use conductive silver glue to connect the two ends of the carbon nanotube membrane to the two electrodes respectively, and then place a piece of glass at a distance of 5mm from the carbon nanotube membrane. Further, evacuate the chamber to 10 - 1 Pa, and keep the vacuum pumping continuously, apply a constant voltage of 20V between the two electrodes, and keep it for 1s. After removing the voltage, the metal film composed of nano-tungsten powder particles is evenly deposited on the lower surface of the upper glass sheet to obtain a nano-tungsten metal film. Fig.10 .
[0088] The above is a detailed introduction to a method for rapid preparation of a nanometal film provided by an embodiment of the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A method for rapidly preparing a nano-metal film, characterized in that: The following steps are involved: S1: acidifying the nanocarbon film, then washing and drying it; S2: preparing a metal particle dispersion; S3: placing a metal particle dispersion on the dried nano-carbon film for loading, and taking it out after drying to obtain a nano-carbon film loaded with a metal particle raw material layer; S4: placing the nanocarbon film loaded with the metal particle raw material layer between two electrodes in the Joule heat heating chamber, and connecting two ends of the nanocarbon film to the two electrodes respectively; S5: placing the substrate on the nanocarbon film loaded with the metal particle raw material layer without contacting it; S6: evacuating the Joule heat heating chamber and applying voltage to the nano-carbon film through a power supply to generate Joule heat, so that the metal particles on the nano-carbon film evaporate to the lower surface of the substrate; S7: Remove the voltage to obtain a nano-metal film.
2. A method for rapidly preparing a nano-metal film, characterized in that: The following steps are involved: S1: acidifying the nanocarbon film, then washing and drying it; S2: Take the metal foil for use; S3: placing the nanocarbon film between two electrodes in a Joule heat heating chamber, connecting two ends of the nanocarbon film to the two electrodes respectively, and placing a metal foil on top of the nanocarbon film; S4: Place the substrate on top of the metal foil without contacting it; S5: evacuating the Joule heat heating chamber and applying voltage to the nano-carbon film through a power supply to generate Joule heat, so that the metal elements on the metal foil evaporate to the lower surface of the substrate; S6: Remove the voltage to obtain a nano-metal film.
3. The method for rapidly preparing a nano-metal film according to claim 1, characterized in that: In step S1, the acidification treatment refers to treatment with nitric acid.
4. The method for rapidly preparing a nano-metal film according to claim 1, characterized in that: In step S2, the metal particle dispersion is prepared by placing metal particles in deionized water, stirring and then ultrasonically dispersing to obtain the dispersion, wherein the metal particle material is one of copper, zinc, aluminum, titanium and tungsten.
5. The method for rapidly preparing a nano-metal film according to claim 1, characterized in that: In step S3, the metal particle dispersion refers to an aqueous ion dispersion of copper powder, zinc powder, aluminum powder, titanium powder or tungsten powder.
6. The method for rapidly preparing a nano-metal film according to claim 1, characterized in that: In step S5, the substrate is placed 5-8 mm above the nano-carbon film loaded with the metal particle raw material layer.
7. The method for rapidly preparing a nano-metal film according to claim 1, characterized in that: In step S6, the Joule heat heating chamber is evacuated to 10 -1 Below Pa.
8. The method for rapidly preparing a nano-metal film according to claim 1, characterized in that: In step S5, the substrate material is a carbon nanotube film, a silicon wafer, a non-conductive glass sheet, a ceramic, or a plastic; in step S6, a voltage is applied to the nanocarbon film through a power source to generate Joule heat, so that the surface temperature of the nanocarbon film reaches 850°C-1050°C, and metal particles evaporate to the lower surface of the substrate.
9. The method for rapidly preparing a nano-metal film according to claim 1, characterized in that: In the step S1, the nanocarbon film refers to one of a carbon nanotube film, a graphene film, a MXene film, and a carbon fiber film.
10. The method for rapidly preparing a nano-metal film according to claim 2, characterized in that: In step S1, the nanocarbon film refers to one of a carbon nanotube film, a graphene film, a MXene film, and a carbon fiber film, and the acidification treatment refers to treatment with nitric acid; In step S2, the metal foil refers to copper foil; In step S4, a substrate is placed 5-8 mm above the metal foil; the substrate material is a carbon nanotube film, a silicon wafer, a non-conductive glass sheet, ceramics, or plastic; In step S5, the Joule heat heating chamber is evacuated to 10 -1 Pa, and applying voltage to the nano-carbon film through a power source to generate Joule heat; the surface temperature of the nano-carbon film reaches 850° C.-1050° C., so that the metal elements on the metal foil evaporate to the lower surface of the substrate.